How Does Being under the Influence Affect Willingness to Experience Overlapping Effects of Alcohol and Marijuana? - Dodge, Tonya; Hoffman, Rebecca K.; Kracke-Bock, Jonah; Jaccard, James J.; Stock, Michelle L. (Substance use & misuse, 2023)
This study tested how individuals anticipate they will respond to opportunities to engage in simultaneous alcohol and marijuana (SAM) use. Two studies utilizing a within-subjects design were conducted. Study 1 was conducted in Spring 2021 and a replication (Study 2) was conducted in Fall 2021. Participants were presented with pairs of scenarios. One scenario pair compared how willing participants expected to be to get drunk if they were sober vs. high. Another pair compared how willing participants would be to take a hit of marijuana if they were sober vs. drunk. College attending young adults (Study 1: N = 173; female = 81%; Study 2: N = 212; female = 49.1%) with varying degrees of substance use experience were recruited. In Study 1 participants reported greater willingness to get drunk when sober than when high. This was qualified by a statistically significant interaction whereby differences were greater among those who had more experience with past 30-day heavy drinking. Similar findings emerged for willingness to use marijuana. Participants anticipated greater willingness to use marijuana when sober than when drunk. This was also qualified by a statistically significant interaction whereby differences were greater among experimental or established users of marijuana than among abstainers. Study 2 findings replicated those from Study 1. College attending young adults state greater willingness to remain under the influence of one substance than to engage in SAM use when opportunities arise. Simultaneous use of alcohol and marijuana among college students is likely an exception, not the rule. Implications for prevention are discussed.